2020
DOI: 10.1542/hpeds.2019-0218
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Children’s Hospitals From Non–Children’s Hospitals in Large Claims Data

Abstract: BACKGROUND:The first methodologic step needed to compare pediatric health outcomes at children's hospitals (CHs) and non-children's hospitals (NCHs) is to classify hospitals into CH and NCH categories. However, there are currently no standardized or validated methods for classifying hospitals. The purpose of this study was to describe a novel and reproducible hospital classification methodology.METHODS: By using data from the 2015 American Hospital Association survey, 4464 hospitals were classified into 4 cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…We used a previously described rigorous method to classify hospitals as either CH or NCH based on AHA survey results, publicly available data, and proportion of pediatric discharges based on HCCI data to validate the classifications. 21 Multiple sensitivity analyses were performed to compare CH-A with CH-B and with NCH and so on, and we found consistent results. 21 Finally, CH may receive higher payments than NCH on routine surgical procedures because of higher costs and lower reimbursements associated with pediatric populations.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We used a previously described rigorous method to classify hospitals as either CH or NCH based on AHA survey results, publicly available data, and proportion of pediatric discharges based on HCCI data to validate the classifications. 21 Multiple sensitivity analyses were performed to compare CH-A with CH-B and with NCH and so on, and we found consistent results. 21 Finally, CH may receive higher payments than NCH on routine surgical procedures because of higher costs and lower reimbursements associated with pediatric populations.…”
Section: Discussionsupporting
confidence: 61%
“…CH were distinguished from NCH using a previously described method. 21 In brief, hospitals were categorized using a combination of self-reported pediatric services on the American Hospital Association (AHA) Survey followed by validation using publicly available data on hospital membership in various pediatric programs such as the Children's Hospital Association, Children's Oncology Group, and American College of Surgeons National Surgical Quality Improvement Program-Pediatric. Using this methodology, 3 tiers of hospitals were created.…”
Section: Hospital Classificationmentioning
confidence: 99%
“…We examined the following 4 definitions of pediatric ED: (1) pediatric admission capability, 7 (2) physically distinct pediatric area in the ED, 6 (3) membership in the CHA, 14 and (4) volume of pediatric ED visits. 3 For pediatric admission capability, we collected data on both pediatric bed availability as measured by the AHA survey and the presence of inpatient care for children as identified by SID pediatric admissions.…”
Section: Discussionmentioning
confidence: 99%
“…6 Others have used volume-based cutoffs (eg, >75% pediatric visits) 3 or the Children's Hospital Association (CHA) list of pediatric facilities. 5 A recent study used data from the America Hospital Association (AHA) survey on self-reported pediatric services 7 to determine the categorization of pediatric and nonpediatric hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In addition, we need to move away from classifying hospitals as "academic" or "nonacademic" because institutions across hospital settings are involved in many academic pursuits, as evidenced through diverse participation within national networks such as the Value in Inpatient Pediatrics Network. 9 In an attempt to define the categories of children' s and nonchildren' s hospitals, Piper et al 10 developed a 4-tiered approach on the basis of hospital characteristics and resources. They defined children' s hospitals as tier A (hospitals that primarily serve children) and tier B (non-tier A hospitals with a pediatric emergency department, NICU, and PICU).…”
Section: Steps Toward Representing the Diversity Of Practice Within Inpatient Pediatric Acute Carementioning
confidence: 99%